Acute intraoperative echocardiographic changes after transapical off-pump mitral valve repair with NeoChord implantation. (15th April 2018) - Colli, Andrea; Besola, Laura; Montagner, Matteo; Soriani, Nicola; Manzan, Erica; Bizzotto, Eleonora; Zucchetta, Fabio; Azzolina, Danila; Bellu, Roberto; Sarais, Cristiano; Pittarello, Demetrio; Gerosa, Gino
Abstract: Objectives: Our aim is to investigate the acute intraoperative effects of the NeoChord repair procedure on mitral valve (MV) annular geometry and LV function and the impact of these changes on MR at 1-year follow-up. Background: Recently transapical off-pump mitral valve repair with NeoChord implantation has been demonstrated to be safe and effective in patients with degenerative mitral regurgitation (DMR). Methods: We retrospectively analyzed baseline and early postoperative 3-dimensional transesophageal echocardiography of 66 patients who underwent NeoChord repair for isolated posterior leaflet MV disease using semiautomatic off-line analysis software. Results: We observed a significant acute reduction of indexed LV end diastolic volume (Δ% = 14, p  < .001), LV ejection fraction (Δ = 5.7%, p  = .002), indexed left atrial volume (Δ = 14.7%, p  = .045), and pulmonary artery pressure (Δ = 2.1%, p  = .026). Among MV geometric parameters, we observed a significant reduction of MV antero-posterior diameter (Δ = 7%, p  < .001), sphericity index (Δ = 8%, p  < .001), annulus circumference (Δ = 0.9%, p  = .021), and annulus area (Δ = 2.7%, p  = .018). At 1-year, 53 patients (85.5%) presented MR ≤ mild, while 9 patients (14.5%) had MR ≥ moderate. Reduction of AP diameter (OR = 0.14, CI −3.83; 0.08, p  < .001), annulus circumference (OR = 0.27, CI −2.98; 0.37, p  = .005), MV area (OR = 0.39, CI −2.46; 0.61, p  = .04), aorto-mitral angle (OR = 0.38, CI −2.49; 0.54, p  = .002) and iEDV (OR = 0.44, CI −2.44; 0.81, p  = .001) were independent protective factors against recurrence of MR greater than mild at 1-year follow-up. Conclusions: Transapical NeoChord repair produces important acute intraoperative changes in MV anatomy in DMR patients. The acute changes observed were associated with procedure durability at 1-year FU. Highlights: NeoChord Mitral Valve (MV) repair results in immediate physiological restoration of the MV anatomy in patients with degenerative MV disease while respecting the dynamic shape of MV. These acute intraoperative changes, in particular the reduction of AP diameter, are associated with procedure durability at 1-year follow-up. The physiological annular shape restoration is significantly greater than what described with other leaflet repair therapies demonstrating that the underlying mechanism is the acute ventricular and atrial volume reduction determined by the mitral regurgitation correction.